PENGARUH KEPERCAYAAN, KEMUDAHAN MENGOPERASIKAN LAYANAN DAN RESIKO BELANJA ONLINE TERHADAP NIAT BELI MELALUI JEJARING SOSIAL - Haris, Abdul (Department of Management, 2014)
The research aims to analyze the effect of the rust, website usability, and the risk of online shopping on intentions to buy in social media. The analytical tool used in this research was a multiple linear regression with SPSS. The result shows that trust, website usability, and the risk of online shopping have a simoultaneously and partially influence on intention to buy. The practical implication is the F irm should provide more attention to trust, website usability, and the risk of online shopping. Its could be increasing sales and the consumer F eels safe and comfortable in the process of online shopping transactions.Keywords: trust, the easy of service operating, the risk of online shopping, purchase intention.